A Comparative Review on Data Hiding Schemes - Din, Roshidi; Sabri, Raihan Sabirah; Mustapha, Aida; Utama, Sunariya (Institute of Advanced Engineering and Science, 2018)
Data hiding is a technique used to protect confidential information.The aim of a particular data hiding scheme is to make a more secure and robust method of information exchange so that confidential and private data can be protected against attacks and illegal access. The aim of this paper is to review on different data hiding schemes, covering the decoding, decrypting and extracting schemes.This paper also highlighted three major schemes that are widely used in research and real practice.The discussion include findings on the most recent work on decryption schemes.